PENERAPAN STRATEGI PEMBELAJARAN KONTEKSTUAL BERBASIS TRI PARARTHA DALAM MENUMBUHKAN NILAI-NILAI ETIKA DAN MORAL SISWA DI SD NEGERI 1 TEGAL TUGU - Wira Bawana, Dewa Gede Satria (UHN IGB Sugriwa Denpasar, 2025)
Abstract This study aims to analyze the implementation of contextual teaching and learning strategies based on Tri Parartha values in shaping students’ ethics and morals at SD Negeri 1 Tegal Tugu. The Contextual Teaching and Learning (CTL) approach connects subject matter to students' real-life experiences, making learning more meaningful and relevant. The Tri Parartha values Asih (compassion), Punia (social generosity), and Bhakti (devotion) are integrated into lesson plans, learning activities, and assessments through thematic approaches, collaborative projects, and reflective practices. This research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that teachers, school leaders, and the school environment play crucial roles in internalizing these values among students. Teachers act as facilitators and role models of the values, while the principal provides weekly guidance emphasizing the importance of Tri Parartha, and the school culture supports value formation through its policies and facilities. Students demonstrated significant behavioral improvements in helping others, discipline, responsibility, and respect. The conclusion of this study is that the contextual teaching and learning strategy based on Tri Parartha is effective in instilling students’ ethical and moral values holistically. This approach can serve as a model for character education based on Hindu religious values that is applicable, contextual, and sustainable, particularly at the primary school level. Keywords : Learning Strategy, Tri Pararta, Ethics and Morals, Students